Analisis Strategi Pengembangan Potensi Agrowisata - Rozalina Novianty; Febriawan Ardi Nugroho (Neolectura, 2022)
This research used survey method data on the number of tourists, the number of star fruit sales, the number of processed star fruit sales per month from May 2019 to April 2021. The sample used 24 observations. The sampling technique used Convinience Sample. The results of the research found that 1) the development of the number of star fruit agro-tourism tourists in May 2019 to April 2021 is negative, (2) The development of star fruit sales from May 2019 to April 2021 fluctuates with a value of IDR 39,320,000, and the weight sold is 3,932 kilograms, (3) Development of fruit juice minus growth with an average of -6.23% per month. The growth of star fruit dodol sales was in a minus growt condition with an average of -14.7% per month. The development of starfruit fruit sales is in minus growt conditions with an average of -8.7% per month, (4) The constraints faced in the development of starfruit agro-tourism :Pokdarwis are still oriented towards economic development local community of Dempel Village and have not prioritized outside investors to participate, (5) Overcoming the obstacles encountered in developing the Carambola Agro Tourism in conducting socialization to the people of Dempel Village. (6) Strategy to develop Star Fruit Agro Tourism includes 3 things: Tourism Awareness Group (Pokdarwis) Dempel Village as the subject of development, Tourism Awareness Group (Pokdarwis) Dempel Village plays a role as a mobilizer in creating a conducive environment and Tourism Group (Pokdarwis) Desa Dempel embodies Sapta Pesona in the community.